The effect of a novel toothpaste in children with white spot lesions - YILMAZ, MÜESSER AHU; KARGÜL, BETÜL (My University, 2022)
Objective: To investigate the effect of a novel mineral containing toothpaste in comparison to a fluoride toothpaste in children with white spot lesions.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); TIP, ARAŞTIRMA VE DENEYSEL; MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); MEDICINE, RESEARCH & EXPERIMENTAL; Genel Sağlık Meslekleri; Araştırma ve Teori; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; İncelemeler ve Referanslar (tıbbi); Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Research and Theory; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Reviews and References (medical); Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Remineralization; Calcium glycerophosphate; Fluoride; Saliva buffer; Saliva pH; LOW-FLUORIDE DENTIFRICES; CALCIUM GLYCEROPHOSPHATE; CARIES DETECTION; SILVER NANOPARTICLES; DENTAL-CARIES; CPP-ACP; ENAMEL; DEMINERALIZATION; REMINERALIZATION; BIOFILM; alcium glycerophosphate; Fluoride; Remineralization; Saliva buffer; Saliva pH